PEMAHAMAN PEMILIH TENTANG PASANGAN CALON PEMILIHAN PRESIDEN TAHUN 2024 Studi Pemahaman Pemilih Gen Z terhadap Pasangan Calon Presiden dalam Pemilu 2024 di Kota Padang Kota Padang - Winada, Kharisma; Damsar, Damsar; Alfiandi, Bob (Universitas Mataram, 2025)
This study explores Generation Z voters’ understanding and motives toward presidential candidates in the 2024 election in Padang City, against the backdrop of state intervention issues and the popularity of Prabowo-Gibran’s “gemoy” social media strategy. A qualitative approach was applied using a critical paradigm and Habermas’s hermeneutic analysis, involving 14 Gen Z informants. Findings reveal that candidate pair 01 voters are mainly highly educated individuals driven by rational motives, pair 02 voters are predominantly first-time voters influenced by their environment and the